'They will be afraid to touch you': LGBTI people and sex workers' experiences of accessing healthcare in Zimbabwe—an in-depth qualitative study. Issue 2 (13th April 2017) - Hunt, Jennifer; Bristowe, Katherine; Chidyamatare, Sybille; Harding, Richard
Abstract : Objectives: To examine experiences of key populations (lesbian, gay, bisexual, trans and intersex (LGBTI) people, men who have sex with men (MSM) and sex workers) in Zimbabwe regarding access to, and experiences of, healthcare. Design: Qualitative study using in-depth interviews and focus groups, with thematic analysis. Participants: Sixty individuals from key populations in Zimbabwe. Setting: Participants were recruited from four locations (Harare, Bulawayo, Mutare, Beitbridge/Masvingo). Results: Participants described considerable unmet needs and barriers to accessing basic healthcare due to discrimination regarding key population status, exacerbated by the sociopolitical/legal environment. Three main themes emerged: (1) key populations' illnesses were caused by their behaviour; (2) equal access to healthcare is conditional on key populations conforming to 'sexual norms' and (3) perceptions that healthcare workers were ill-informed about key populations, and that professionals' personal attitudes affected care delivery. Participants felt unable to discuss their key population status with healthcare workers. Their healthcare needs were expected to be met almost entirely by their own communities. Conclusions: This is one of very few studies of healthcare access beyond HIV for key populations in Africa. Discrimination towards key populations discourages early diagnosis, limits access to healthcare/treatment and increases risk of transmission of infectious diseases. Key populations experience unnecessary suffering from untreated conditions, exclusion from healthcare and extreme psychological distress. Education is needed to reduce stigma and enhance sensitive clinical interviewing skills. Clinical and public health implications of discrimination in healthcare must be addressed through evidence-based interventions for professionals, particularly in contexts with sociopolitical/legal barriers to equality.